Polyglycolic acid‐hyaluronan scaffolds loaded with bone marrow‐derived mesenchymal stem cells show chondrogenic differentiation in vitro and cartilage repair in the rabbit model. Issue 7 (10th May 2013) - Patrascu, Jenel M.; Krüger, Jan Philipp; Böss, Hademar G.; Ketzmar, Anna‐Katharina; Freymann, Undine; Sittinger, Michael; Notter, Michael; Endres, Michaela; Kaps, Christian
Abstract In cartilage repair, scaffold‐assisted one‐step approaches are used to improve the microfracture (Mfx) technique. Since the number of progenitors in Mfx is low and may further decrease with age, aim of our study was to analyze the chondrogenic potential of freeze‐dried polyglycolic acid‐hyaluronan (PGA‐HA) implants preloaded with mesenchymal stem cells (MSCs) in vitro and in a rabbit articular cartilage defect model. Human bone marrow‐derived MSC from iliac crest were cultured in freeze‐dried PGA‐HA implants for chondrogenic differentiation. In a pilot study, implants were loaded with autologous rabbit MSC and used to cover 5 mm × 6 mm full‐thickness femoral articular cartilage defects (n = 4). Untreated defects (n = 3) served as controls. Gene expression analysis and histology showed induction of typical chondrogenic marker genes like type II collagen and formation of hyaline‐like cartilaginous tissue in MSC‐laden PGA‐HA implants. Histological evaluation of rabbit repair tissue formation after 30 and 45 days showed formation of repair tissue, rich in chondrocytic cells and of a hyaline‐like appearance. Controls showed no articular resurfacing, tissue repair in the subchondral zone and fibrin formation. These results suggest that MSC‐laden PGA‐HA scaffolds have chondrogenic potential and are a promising option for stem cell‐mediated cartilage regeneration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 1310–1320, 2013.